C reactive protein testing in general practice safely reduces antibiotic use for flare-ups of COPD. (30th December 2019) - Cook, Rob; Lyon-Maris, Johnny; White, Alicia
The study: Butler CC, Gillespie D, White P, et al. C-reactive protein testing to guide antibiotic prescribing for COPD exacerbations. N Engl J Med 2019;381:111-20. This research was funded by the NIHR Technology Assessment Programme (project number 12/33/12). The testing machines used in the study were loaned to researchers by the manufacturer, who also provided training on their use. The manufacturer had no other role in any part of the trial. To read the full NIHR Signal, go to https://discover.dc.nihr.ac.uk/content/signal-000820/crp-testing-safely-reduces-antibiotic-use-for-copd-flare-ups